O Direito à educação de crianças com transtorno do espectro autista a qualificação do acompanhante especializado como fator necessário a inclusão - Carvalho, Flávia Grazielle Rebouças Teixeira de (2018)
The research presented here consists of a study on the education of children with autism spectrum disorder (ASD) and the role of the specialized chaperone as a necessary factor for inclusion. The research is based on the study of the historical trajectory of people with disabilities, its current conceptualization, analyzing in parallel the basic principles pointed out by the Federal Constitution of Brazil, such as Equality and Dignity of the Human Person. Such grounds are considered within our legal system necessary sources of guidance and protection to groups considered minority. In order to do so, the aim is to approach the autism-related theme, verifying its definition, main characteristics and behaviors presented by children who are affected by the syndrome. The investigation attends the study of the fundamental right to education, however, its focus is centered on the provisions of Federal Law n. 12.764/12 (Berenice Piana Law), which establis hes in its text the presence of a "specialized chaperone" in the regular classes of regular education, who should collaborate and act as a facilitator for learning and interaction with other students. The presence of the figure of a qualified professional is a necessary and decisive factor so that the child with autism can be accompanied in a more didactic way, becoming more participatory and able to interact with the completeness of the school environment. However, the specific competence and aptitude of this specialist is not predefined in the said Law, making it possible for educational establishments to admit people without prior knowledge to deal with diversity. With regard to the general objective, the research is explanatory, since it uses a qualitative approach, elaborated from bibliographical and documentary sources, performed through the survey of theoretical references already made.